2012
DOI: 10.5935/0101-2800.20120001
|View full text |Cite|
|
Sign up to set email alerts
|

Nutritional and epidemiological aspects of patients with chronic renal failure undergoing hemodialysis from Brazil, 2010

Abstract: This study characterized Brazilian hemodialysis patients in 2010, and may support further studies to monitor nutrition and epidemiological transitions of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
4
0
2
Order By: Relevance
“…In the current study, we found an association between anemia and hypoalbuminemia and frailty, a similar results were observed by other authors in both community-dwelling older adults [32] and hemodialysis populations [17,29,33]. An increase in the total WBC counts is recognized as a clinical indicator for systemic inflammation, and associated with cardiovascular and cerebrovascular events [34,35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, we found an association between anemia and hypoalbuminemia and frailty, a similar results were observed by other authors in both community-dwelling older adults [32] and hemodialysis populations [17,29,33]. An increase in the total WBC counts is recognized as a clinical indicator for systemic inflammation, and associated with cardiovascular and cerebrovascular events [34,35].…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to the definition of frailty as a geriatric syndrome [1], we observed that the frailty, not only started early in the hemodialysis population with mean age 44y and 45% of patients younger than 40 y were frail but also progress rapidly with aging to 60%; 66% and 73% at age 40-50; 50-60 and 60-70y respectively. Certainly several previous researches were noted similar results [17,20,25] Female gender more liable to frailty, actually several researchers observed such correlation [17,26,27], while others showed that male gender more susceptible to frailty than female [28,29], however such debate may be attributed to the racial difference between those studies Diabetes and severity of secondary hyperparathyroidism as comorbid diseases were associated with frailty. Consisting with previous researches of Johansen et al [17] and Mansur et al [20] respectively.…”
Section: Discussionmentioning
confidence: 82%
“…Results were found in a study 8 , which sought to trace nutritional and epidemiological aspects of chronic renal patients submitted to hemodialysis treatment in Brazil, pointing out that the profile of patients has been presenting a high age group. Considering that there is a significant increase in chronic diseases, especially CKD, associated with the high age groups of this population and the longevity of the Brazilian and world population, the available treatments are proving to be more effective and able to offer quality patients.…”
mentioning
confidence: 99%
“…Diferente dos resultados do Censo de diálise, o presente estudo demonstrou que 18,1% dos pesquisados apresentavam idade >60 anos. Resultados semelhantes foram encontrados no estudo de Biavo et al 21 . Com relação à adequação da diálise, o Kt/V esteve dentro do recomendado em 93,1% dos pacientes com média de 1,5±0,2, dado importante já que, diálise insuficiente está associada ao acúmulo de toxinas urêmicas, o que contribui para alterações gastrointestinais, interferindo no apetite, causas de desnutrição 13 .…”
Section: Discussionunclassified